The Implementation of Activity Sheet Based on Project-Based Learning on Biotechnology Material to Train Bioentrepreneurship Skills for First Grade High School Students - Oktavinda, Alicia; Winarsih, Winarsih (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2024)
The Merdeka Curriculum is implemented to develop 21st century skills, one of which is entrepreneurial skills. The field of Biology study that is integrated with the concept of entrepreneurship is called Bioentrepreneurship. Bioentrepreneurship skills can be trained through implementing the Project Based Learning (PjBL) learning strategy using the help of student activity sheets (LKPD) adapted from the LKPD developed by Amalia (2023). This research aims to describe 1) the implementation of learning, 2) students' Bioentrepreneurship skills, and 3) students' responses to the implementation of Project-Based Learning LKPD on biotechnology material. This research was conducted at SMAN 2 Lamongan in class The parameters used to collect data include 1) implementation of learning, 2) Bioentrepreneurship skills, 3) student response. The research data were analyzed using quantitative descriptive analysis methods. The results showed that 1) the implementation of learning carried out by teachers was very good, amounting to 95.8%, 2) 94.5% of students implemented Bioentrepreneurship skills very well and achieved indicator completion with details of the percentage increase per indicator exploring, planning, producing, communicating, and reflecting respectively at 51.4%, 52.7%, 54.2%, 38.2%, and 42%, 3) student responses to LKPD were 95.73% or very positive. Thus, it can be concluded that the application of PjBL LKPD in biotechnology material can significantly train Bioentrepreneurship skills in class X high school students. Students are expected to demonstrate strong learning motivation, engage in active learning, and have Bioentrepreneur skills that suit their current and future needs.